Case Report: Small bowel metastasis from esophageal squamous cell carcinoma: a case series and systematic review of clinical characteristics, tropism, and survival outcomes - Mingyu Zhou; Yunjun Liu; Huifang Huang; Xia Chen; Qiwen Huang; Shaowei Huang; Zhichao Yan; Yuyin Chen; Junming Lin; Jiayi Huang; Guankao Xie; Yating Hou; et al. (Frontiers in Immunology, 2026)
Background Small bowel metastasis from primary esophageal carcinoma is a rare occurrence, typically indicative of advanced disease and often presenting with non-specific abdominal symptoms. Failure to consider this possibility in the differential diagnosis may lead to delayed or incorrect management. This article reports the case of a 60-year-old male with small bowel metastasis originating from esophageal squamous cell carcinoma. To better characterize this clinical entity, we also conducted a systematic review of 23 documented cases, analyzing their clinicopathological features, diagnostic approaches, treatment modalities, and prognostic outcomes. Case presentation A 60-year-old man presented with small bowel obstruction, ultimately diagnosed as metastatic esophageal squamous cell carcinoma. Surgical resection was followed by combined immunotherapy and chemotherapy, yielding a partial response. Systematic review We reviewed 23 published cases, highlighting a strong male predominance (82.6%), jejunal predilection, and a median survival of only 6 months post-diagnosis. Small bowel metastasis from esophageal carcinoma, though uncommon, represents a challenging clinical scenario often mimicking more common abdominal pathologies. Histopathological confirmation is essential for accurate diagnosis. Early detection and a multidisciplinary treatment approach may correlate with favorable survival trends in these advanced-stage patients. Conclusions Small bowel metastasis should be considered in esophageal cancer patients with acute abdominal symptoms. Histopathological confirmation is crucial, and a multimodal approach may be associated with extended survival trends in selected patients.